Evaluation of lean practices in warehouses: an analysis of Brazilian reality - Caroline Pereira and Rosley Anholon and Izabela Simon Rampasso and Osvaldo Luiz Goncalves Quelhas and Walter Leal and Luis Antonio de Santa-Eulalia (The international journal of productivity and performance management : IJPPM, 2020)
Purpose This article aims to investigate the most applied lean warehouse practices in Brazilian warehouses. Design/methodology/approach To perform this research, three phases were conducted: a literature review, a multiple case study, and an analysis of lean warehouses practices implementation by an engineering committee. Thus, both qualitative and quantitative approaches were used. Additionally, the study has an applied nature, with an exploratory and descriptive character. Findings Results showed that regardless of the type of criterion used, the most implanted practices are those that do not involve investments in technology. On the other hand, practices like RFID and Cross Docking systems were not found in any of the operations, which shows numerous possibilities for improvement. Originality/value The main contribution of this article is to initiate a debate about the management and productivity of Brazilian warehouses, a theme still little explored by the academic community despite the importance that the logistic scenario represents for Brazil as an emerging country and leader in Latin America, participating actively in several global supply chains.